Determination of trichlorfon residues in vegetables using a quantum dot-labeled biomimetic immunoassay method followed by capillary electrophoresis. Issue 6 (2nd November 2017) - Jiang, Mingdi; Wu, Shang; Xu, Longhua; Qiao, Xuguang; Xu, Zhixiang
ABSTRACT: In this study, a molecularly imprinted polymer that could selectively recognize trichlorfon was synthesized. Using the imprinted polymer as biomimetic antibody, a novel biomimetic immunoassay-capillary electrophoresis method with improved sensitivity was developed for the detection of trichlorfon. This method was based on the competitive reaction between quantum dot-labeled trichlorfon and free trichlorfon with the biomimetic antibody. Under optimal conditions, the limit of detection (IC15 ) and the sensitivity (IC50 ) of the method was 0.35 ± 0.021 μg/L and 0.81 ± 0.025 mg/L, respectively. To evaluate the accuracy of the method, trichlorfon spiked in the carrot and zucchini samples was determined, and the recovery was in the range of 80.1–95.3%. This method was also applied to the quantitative detection of trichlorfon residues in the edible rape and leek samples, and the results had a good correlation with those obtained using a gas chromatography method.